Copyright-proof network-based video recording services? - Alén-Savikko, Anette (Javnost (Ljubljana), 2016)
Late in 2014, a government bill on amendments to the Finnish Copyright Act was introduced to Parliament. One of the amendments proposed concerned new provisions for copyright-proofed network-based recording services. Early the same year, a few core players in the field successfully concluded negotiations on the matter. These players included broadcasters, tele-operators and collecting societies. The bill introduced a new provision on extended collective licence tailored for network-based recording services. The amending Act entered into force on 1 June 2015. Accordingly, the services must be based on contracting with both broadcasters and organisations representing copyright holders. By force of law, the effects are extended also to right holders beyond direct representation. This solution largely follows the initial proposal put forward by the core players. In this article, the Finnish solution will be analysed in a theoretical framework. Alongside new technologies, the focus is on democracy and citizenship in the information society. The article asks: what are the demands that the amendments to the Copyright Act are supposed to meet? What is the role of information society citizens in the setting? In answering these questions, the article draws on the dichotomy between democratisation of culture and cultural democracy.
Keywords: Avtorske pravice; Copyright; Democratization; Demokratizacija; Informacijska družba; Information society